Wind waves and the reaeration coefficient in open channel flow: technical report - Eloubaidy, Aziz F., author; Plate, Erich J., author; Gessler, Johannes, author; Fluid Dynamics and Diffusion Laboratory, Civil Engineering Department, Colorado State University, publisher (Colorado State University. Libraries, 1969)
The reaeration rates with and without wind blowing along the water surface have been studied in the laboratory. The reaeration results, without wind, have been compared with those obtained by previous investigators. Based on the concept that the reaeration rate is controlled by an effective turbulent diffusion coefficient at the surface and by rate of surface renewal, an equation was developed to predict reaeration rates in natural streams and rivers with wind blowing over the water surface. The state of turbulence, beneath the water surface, was considered as a good measure of the rate of surface renewal. The experimental results gave support to the theoretically developed equation. The properties of water surface give good agreement with the results reported by previous investigators. Experimental results indicate that reaeration rates are significantly increased when waves appear on the surface. The increase is very much more than can be accounted for by the increase in surface area. The increase was attributed to the dynamic effect of separation, occurring at the lee side of the waves.
CER69-70AFE2.
August 1969.
Prepared under National Science Foundation Grant No. GK 2142.
Keywords: Hydrodynamics; Wave-motion, Theory of; Water -- Aeration